Landslide susceptibility mapping of the Main Boundary Thrust (MBT) region in Tinau-Mathagadhi Section of Palpa District, Lumbini Province - Paudyal, Kabi Raj; Maharjan, Rupendra (Journal of Nepal Geological Society, 2022)
The study was carried out in Tinau-Mathagadhi section of Palpa District, Lumbini Province. The output of the landslide susceptibility analysis using frequency ratio (FR) is evaluated. Google Earth (CNES/Airbus and Maxar Technologies) Imagery of 50 cm spatial resolution was used to detect landslides. Data training and testing sampling was created using the landslide inventory. Eight causative factors were derived from topographic, geological, and land-use maps. The causative factors and training events were used to determine the FR ratings. The objective of present study is to address the effect of the Main Boundary Thrust (MBT) along with other important parameters in landslide susceptibility mapping. The integration of causative factors that assigned FR scores yielded the landslide susceptibility map. The validation of 79.6% was obtained using the ROC-AUC curve. Among eight causative factors, it was found that distance from the Main Boundary Thrust (MBT), aspect, land-use, and geology are dominating factors in the occurrence of the landslide. The FR method is based on a quantitative relationship between landslide inventory and landslide affecting factors. The method is valid for Tinau-Mathagadhi section and MBT is one of the causes of landslides in this area.